A comparative study of the social studies program of the secondary schools in the Philippines and in Thailand - Rujirachunha, Rabiab 1933- ([Quezon City s.n.], 1962)
This is a comparison of the present programs of secondary school social studies in the Philippines and in Thailand, based on the goals, the social studies courses set up to achieve the goals, the methods of instruction commonly used, and the materials of instruction available.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Social sciences -- Study and teaching (Secondary)